1993
DOI: 10.1111/j.1440-1754.1993.tb00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Widal test in diagnosing childhood typhoid fever in endemic areas

Abstract: Data are presented for 2382 children investigated for fever in a Malaysian hospital between 1984 and 1987 when Widal tests and blood cultures were a routine part of every fever screen. There were 145 children who were culture positive (TYP-CP) for Salmonella typhi, while 166 were culture negative but were diagnosed as having typhoid (TYP-CN). Analyses of the sensitivity and specificity of combinations of initial Widal titres in predicting a positive S. typhi culture in a febrile child (culture positive vs the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…In contrast to findings from other parts of Asia, [19][20][21][22] our data support the contention that the Widal test has poor diagnostic value in children with typhoid fever. 23,24 Most of the children presented in the second week of their illness and we used a cut-off titer of 1:80.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast to findings from other parts of Asia, [19][20][21][22] our data support the contention that the Widal test has poor diagnostic value in children with typhoid fever. 23,24 Most of the children presented in the second week of their illness and we used a cut-off titer of 1:80.…”
Section: Discussioncontrasting
confidence: 57%
“…Six reported blood culture data from populations in whom minimal or no selection criteria were applied (included in this group are studies with no selection criteria for children aged <5 years but minimal criteria for those aged ≥5 years), four studies reported data from selected populations and two were case‐series. Among studies which considered the unselected group, only 2/6 report prevalences >1%, with 5.51% prevalence in Dhaka, Bangladesh and 6.1% in Malaysia (Choo et al. 1993; Sinha et al.…”
Section: Resultsmentioning
confidence: 99%
“…Choo et al [21]. considered all febrile cases with an S.typhi negative blood culture as the control group which is problematic as a number of blood culture-negative results are likely to be false-negative due to the poor sensitivity of the blood culture [17-19,22]. Furthermore, it is difficult to compare the different test kits, as varying antigens perform differently [23].…”
Section: Discussionmentioning
confidence: 99%